Resistência de Conyza spp. ao herbicida glifosato: distribuição geográfica, aspectos anatômicos, genéticos e moleculares - Schneider, Theodoro (2018)
The genus Conyza belonging to the family Asteraceae, comprises important weeds known as "buvas". Among them, stand out C. canadensis, C. bonariensis and C. sumatrensis. They often infest growing areas as well as uncultivated areas. The emergence of herbicide resistant weed biotypes is conditioned by the genetic change in the population, imposed by selection pressure through the application of herbicides with the same mechanism of action. Therefore, the objectives of this research were to evaluate the distribution of buff biotypes resistant to glyphosate herbicide in the States of Rio Grande do Sul, Paraná and Mato Grosso do Sul; to identify the chemical alternatives for control of glyphosate resistant buff, applied at different stages of development; to perform the anatomical description of the biotype resistant and susceptible to glyphosate leaf; to analyze the genetic similarity in C. sumatrensis biotypes from different regions of Brazil; and to investigate the resistance mechanism of biotypes of C. sumatrensis resistant to herbicide glyphosate by determining the expression levels of EPSPs genes encoding the EPSPs enzyme, M11 and M7 genes of ABC carrier proteins. For this, experiments were conducted in greenhouse, field, and laboratory, using seeds of Conyza spp. collected in different locations in Rio Grande do Sul, Paraná and Mato Grosso do Sul. We evaluated 137 biotypes of Conyza spp. as well as the geographic distribution of the resistance, applying the glyphosate herbicide in the 4 to 6 leaf stage, and evaluating the herbicide response determining the resistance. In the field two experiments were conducted in the 2016/17 and 2017/18 crops, where several herbicides belonging to different mechanisms of action were used to identify different control alternatives of Conyza spp. For the anatomical analysis, leaves of two populations of C. sumatrensis resistant to glyphosate and another susceptible were collected. The determination of the thickness of the epidermis on the adaxial face of the leaves of the biotypes and the diameter of the main vascular bundles were performed. Through microsatellite molecular markers the genetic similarity between C. sumatrensis biotypes from different geographical regions was analyzed, using 19 molecular markers, and compared by means of agarose gel. For the investigation of resistance mechanism in glyphosate resistant C. sumatrensis biotype, the level of expression of the EPSPs, M11 and M7 genes in resistant and susceptible biotypes was compared. RNA was extracted from the biotypes and the expression of the genes was compared by means of real-time PCR (RT-qPCR). It was obtained as results, that 78% of the biotypes of Conyza spp. tested showed resistance to glyphosate herbicide. Plants of buff up to 5 cm are controlled with the herbicides glyphosate + saflufenacil, paraquate, diquat and glufosinate of ammonium, already plants between 6 and 15 cm are controlled with the same treatments, except Paraquate. No anatomical differences were found in the biotypes evaluated in this study. The analysis of genetic similarity evidenced a diversity of biotypes, forming two groups, one formed by a susceptible biotype and the other by glyphosate - resistant biotypes. The M7 and M11 genes presented higher relative expression in the resistant biotype, associating the mechanism of resistance to the sequestration of the herbicide in the vacuole.